FAKTOR-FAKTOR YANG MEMPENGARUHI TAX AVOIDANCE PADA PERUSAHAAN SEKTOR KONSUMEN PRIMER - Jessica; Yuniarwati (Jurnal Paradigma Akuntansi, 2025)
The purpose of this study is to know the effects of profitability, leverage, firm size, and institutional ownership on tax avoidance of consumer non-cyclicals companies listed on the Indonesia Stock Exchange in 2019-2021. The method in this study is using purposive sampling. The samples used 40 companies consisting of the sub-sector of food & staples retailing, food and beverage, tobacco, nondurable household products. Data were processed and tested using Microsoft Excel 2019 and E-views version 10. The result of this study shows that profitability has a significant negative influence on tax avoidance and that leverage has a significant positive influence on tax avoidance, while firm size and institutional ownership have no influence on tax avoidance.